Characterization and comparison of thin ply IM7/8552 composites processed by automated tape placement and hand layup. (June 2023) - Balaga, Uday Kiran; Gargitter, Verena; Crane, Roger; Tierney, John; Yarlagadda, Shridhar; Heider, Dirk; Advani, Suresh G.
Manufacturing of large composite structures is labor-intensive and challenging. Traditional processing methods can be replaced by automated approaches such as Automated Tape Placement (ATP). The focal point of this effort is on thin-ply thermoset prepreg materials which have shown better resistance to damage tolerance under applied stress when compared to standard ply-thickness materials in recent times. However, composites processed by thin-ply materials require more placement iterations to achieve the same net volume of coverage as the standard ply-thickness materials. This can increase the probability of placement defects such as gaps and overlaps, which may degrade the mechanical performance of the composite. Modifications to the existing ATP system are made to address the issues of placement defects, which resulted in improved accuracy for thin ply placement. Unidirectional and quasi-isotropic panels are fabricated from 12'' wide unidirectional prepreg sheet with the conventional hand layup (CHL) method for the baseline property comparison with panels fabricated by the ATP process using a ¼'' wide slit tape. This paper investigates the effects of processing defects and material variability on the mechanical properties such as tensile, Open hole tension and Bearing tests of thin ply composites. In addition, the microstructure of the fabricated thin-ply composite panels is analysed using ultrasonic C-scans and confocal microscopy to examine the processing and material quality.